Micro-flow facility for traceability in steady and pulsating flow. (August 2015) - Bissig, Hugo; Tschannen, Martin; de Huu, Marc
Abstract: This paper describes a primary standard for liquid micro-flow, which covers the flow rate range from 1 ml/min down to 100 nl/min with uncertainties in the range from 0.1% to 0.6% (coverage factor 95%). To realize stable flow rates, METAS applies the principle of generating flow by means of a constant pressure drop over a capillary tube according to the law of Hagen–Poiseuille. The constant pressure drop is mainly possible due to the fact that the relative pressure at the outlet needle remains constant as the outlet needle is positioned just above the beaker collecting the water. The special beaker and the adjustments for the weighing zone to control evaporation will be discussed in the paper as well as measurement results from flow sensors and flow generators, which highlight the repeatability and the reproducibility of the facility. Highlights: Primary standard for liquid flow rates from 1 ml/min to 100 nl/min is described. The dynamic gravimetric method is applied to determine mass flow rate. Traceability in steady and pulsating liquid flow.